PATCHOULI ALCOHOL ENRICHMENT FROM PATCHOULI OIL USING MOLECULAR DISTILLATION UNIT - Joddy Arya Laksmono, Egi Agustian dan Indri Badria Adilina (Jurnal Teknologi Industri Pertanian, 2007)
ABSTRACT Molecular distillation in the vacuum pressure about 10-3 mbar, temperature in the range of 80 oC – 100 oC, and wiper rate between 60 – 80 rpm was used for the separation and purification of patchouli oil. Patchouli oil has a large composition of patchouli alcohol which is usually used as a fixative for perfumery, cosmetics and pharmaceuticals. A large composition of patchouli alcohol usually is in the residue due to the high boiling point of this compound than others. Purification of patchouli alcohol increased with wiper rate and temperature but decreased with the feed rate. The temperature of liquid entering to the unit, feed rate and the wiping element bears on the distillation cylinder due to the centrifugal force and rolls over it bringing the liquid on the distillation cylinder into an intensive complex movement were the important technological parameters that determined distillation operation. Pursuant to condition above produced purification of patchouli alcohol due to the patchouli oil about 73.37%.   Keywords: Patchouli oil, molecular distillation, patchouli alcohol, separation, purification.